Density functional theory study of oxygen vacancy defect diffusion properties in λ-Ta2O5. (3rd December 2020) - Wu, Xinghui; Cui, Nana; Zhang, Qiuhui; Wang, Wenju; Huang, Quanzhen; Zhang, Hongsong; Xu, Qixing
Abstract: The formation energy and diffusion properties of oxygen vacancy defects in λ -Ta2 O5 were studied using first-principle calculations. The calculated formation energy of neutral oxygen vacancy defects was consistent with previous studies carried out, and the charged oxygen defects considering periodic correction were also studied. The calculations obtained showed that the formation energy of +2 charged oxygen vacancy defects was 0.83–1.16 eV. Also, the diffusion activation energy consisting of oxygen vacancy defect formation energy and diffusion barrier concurred well with the diffusion activation energy measured by experiments. A linear relationship was found between the diffusion barrier and the diffusion distance.